2018
DOI: 10.1177/1569186118764065
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Japanese version of the Westmead Home Safety Assessment for the elderly in Japan

Abstract: ObjectiveHome safety assessment and intervention is a key component in the management of fall risk in elderly people. However, a standardised assessment for home safety has not yet been established in Japan. We developed a Japanese version of the Westmead Home Safety Assessment by partially modifying the original version according to house structures and lifestyles in Japan and examined its inter-rater reliability and content validity.MethodsJapanese elderly in the community who had fear of falls were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…This study also confirmed sufficient reliability, content and factorial validity, as well as clinical utility (Lai et al, 2019). The WeHSA was developed as a tool for occupational therapists to identify environmental hazards in the homes of older persons who are at risk of falling (Hasegawa & Kamimura, 2018). The original version has been evaluated as a reliable tool (Clemson et al, 2010; and there is evidence supporting the content validity .…”
Section: Housing Assessment Tools Identifiedsupporting
confidence: 60%
See 4 more Smart Citations
“…This study also confirmed sufficient reliability, content and factorial validity, as well as clinical utility (Lai et al, 2019). The WeHSA was developed as a tool for occupational therapists to identify environmental hazards in the homes of older persons who are at risk of falling (Hasegawa & Kamimura, 2018). The original version has been evaluated as a reliable tool (Clemson et al, 2010; and there is evidence supporting the content validity .…”
Section: Housing Assessment Tools Identifiedsupporting
confidence: 60%
“…The selection procedure resulted in a final inclusion of 22 articles (Chin et al, 2013;de Guzman et al, 2013;Eshkoor et al, 2013;Hasegawa & Kamimura, 2018;Kamei et al, 2015;Kittipimpanon et al, 2012;Lai et al, 2019;Lee & Yoo, 2015;Leung, 2019;Lin et al, 2007;Matchar et al, 2019Matchar et al, , 2017Mitoku & Shimanouchi, 2014;Pattaramongkolrit et al, 2013 Safety house checklist (Carter et al, 1997); Home-screen scale (Johnson, et al, 2001) C. 2008; Romli et al, 2016Romli et al, , 2018Sophonratanapokin et al, 2012;Sukkay, 2016;Tan et al, 2018;Tongsiri et al, 2017). A summary of the included articles is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations